ANALYSIS OF MARKETING COSTS, PROFIT MARGINS AMONG ACTORS, MARKETING CHANNEL EFFICIENCY, AND FARMER'S SHARE DISTRIBUTION IN THE PALM OIL MARKETING SYSTEM: A LITERATURE REVIEW BASED ON A VALUE-ADDED APPROACH - Farida Akbarina; Tehedi Tehedi (Adisam Publisher, 2026)
This study analyses marketing costs, profit margins between actors, marketing channel efficiency, and farmer's share distribution in the Indonesian palm oil marketing system through a literature review. The results show high marketing costs of Rp450-1,200/kg (22-30% of the fresh fruit bunch price), margin disparities (farmers 25-35% vs mill 35-42% added value), average channel efficiency of 24.6% (ideal <15%), and a national farmer's share of 71.4% (standard >80%) due to long supply chains and local oligopsony. The value-added approach reveals a redistribution potential of 12-18% through channel shortening, e-FFB trading digitalisation, and plasma partnerships recommended to increase systemic efficiency by 15-20% and the welfare of farmers managing 40% of the national area